DEPOSITIONAL MODEL OF NGRAYONG FORMATION IN MADURA AREA, NORTH EAST JAVA BASIN, INDONESIA - Paike Htwe; Sugeng Sapto Surjono; Donatus Hendra Amijaya; Kyuro Sasaki (Geological Engineering Department Universitas Gadjah Mada, 2015)
The early Middle Miocene Ngrayong Formation, an important reservoir of North East Java Basin, is well exposed in the central anticlinal part of Madura Island. The purpose of current study is to classify the depositional environments of the study area based on the characteristics and geometry of sedimentary facies. In the Madura island, the thicker clastics and deeper carbonates of Ngimbang Formation and Kujung Formation of Late Oligocene-Early Miocene deposited in the northeast-southwest asymmetrical half grabens. After the deposition of Kujung Formation, the basin morphology developed nearly eastwest trending shelf edge and the deposition of Tuban Formation began. The ﬁne grained complex of Tuban Formation was followed by the Ngrayong Sandstones deposition. The depositional model of Ngrayong Formation is being producing of wide variety of depositional environments. Large scale cross-bedded sandstones and bioturbated massive sandstones with thin to medium bedded argillaceous limestone that outcrop in the northern part of the study area are deposited in costal environment. The heterolithic sandstone with planar and trough cross-lamination, ﬁne grained sandstone with interlaminated structure and bioclastic carbonate exposed in the central part of the study area are deposited in upper shallow marine area. Dark grey siltstones and mudstones deposited in lower shallow marine area are well exposed in southern part of the study area. In conclusion, Ngrayong Formation in Madura area is developed in three depositional units which are coastal, upper shallow marine and lower shallow marine.